Antiques ho-ho-homicide - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2018)
To Brandy Borne and her ditzy diva mother, homicide in small-town Serenity is the gift that keeps on taking. But murder turns merry as Brandy and Vivian gather collectible clues in a wintry workshop, seek the grinch who dimmed a pageant star<U+2019>s twinkle, and bag the humbug helper who snuffed a sidewalk Santa. Aided by Sushi, their elfin shih tzu, our seasonal sleuths crumble a bountiful batch of Christmas crookies. And though suspects may show bad will, and good cheer seems in short supply, this collection of Trash <U+2018>n<U+2019> Treasures holiday homicides sparkles as the Borne girls wrap up three frolicsome felonies.